Experimental modelling of a multi-use floating platform for wave and wind energy harvesting. (1st February 2019) - Sarmiento, J.; Iturrioz, A.; Ayllón, V.; Guanche, R.; Losada, I.J.
Abstract: Understanding the hydrodynamic performance of floating energy converters is a complex challenge. Hence, physical modelling is necessary to evaluate the performance of innovative designs and validate them. The present paper shows the experimental work performed to validate a new floating semisubmersible structure which combines wave energy converters (3 Oscillating Water Columns, OWC) and wind harvesting (5 MW wind turbine). To characterize the global response of the platform, as well as the OWCs' performance, an innovative wave tank testing campaign was carried out at the Cantabria Coastal and Ocean Basin (CCOB). The multi-use platform was characterized under the incidence of regular wave tests (with and without wind), operational sea states and survival sea states (combining waves, currents and wind). During the tests wind was reproduced with a portable wind generator and the wind turbine was simulated as a drag disk. The OWC air turbines were experimentally conceptualized by different diameter openings on the upper part of each OWC. This paper describes the experimental testing campaign carried out at the CCOB and presents the most significant experimental results obtained, such as natural periods, movements, loads on the mooring system or accelerations, which are representative of the performance of the multi-use platform presented. Highlights: Multi-use platforms: Combining several energy converters in the same foundation. Wave and Wind Energy converters. Physical modelling of floating structures. Hydrodynamic response and mooring system analysis. Influence of the energy converters over the platform dynamics.